Exploring the career development challenges and expectations of international students during the COVID-19 pandemic - Li, Jason; Liu, Xun; Mullins, Philip (Journal of International Students, 2024)
In this study, the interrelations between locus of control, perceived social support, career decision self-efficacy, and career outcome expectations among international students in the United States during the COVID-19 pandemic was investigated through the lens of Social Cognitive Career Theory (SCCT). Based on structural equation modeling, data from 194 international students at a large Midwestern research institution in the United States. revealed that career decision self-efficacy plays a significant mediating role in the relationships between age, locus of control, and career outcome expectations. These results provide valuable insights into the career development process of international students during a global pandemic. The implications of these findings and directions for future research are thoroughly discussed.